2015
DOI: 10.1160/th14-07-0589
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor in relation to coronary plaque characteristics and cardiovascular outcome

Abstract: High von Willebrand factor (VWF) plasma levels are associated with an increased risk of coronary artery disease. It has been suggested that the increase of VWF levels is partly due to endothelial dysfunction and atherosclerosis. Our aim was to investigate the association between coronary plaque burden, the presence of high-risk coronary lesions as measured by intravascular ultrasound virtual histology (IVUS-VH) and VWF levels. In addition, we studied the association between VWF levels and one-year cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
(48 reference statements)
3
28
0
2
Order By: Relevance
“…[17] Myocardial oxygen supply relative to demand was evaluated with the subendocardial viability ratio (SEVR). [18] Finally, plasma sCD62P and von Willebrand factor (VWF) were evaluated as biomarkers of platelet activation[19] and endothelial cell dysfunction,[20] respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[17] Myocardial oxygen supply relative to demand was evaluated with the subendocardial viability ratio (SEVR). [18] Finally, plasma sCD62P and von Willebrand factor (VWF) were evaluated as biomarkers of platelet activation[19] and endothelial cell dysfunction,[20] respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the European Concerted Action on Thrombosis and Disabilities (ECAT) study [80], in stable patients with angiographically documented coronary artery disease (CAD), higher levels of VWF:antigen (VWF:Ag) were independently associated with an increased incidence of MI and sudden death. More recently, in the ATHEROREMO-IVUS study [81], in patients with stable CAD (SCAD), an increased level of VWF:Ag was associated with higher coronary plaque burden, adverse CV outcome, and death during 1-year of follow-up. VWF is also an independent risk factor for first STEMI: levels of VWF are significantly increased in patients with first ST-elevation myocardial infarction (STEMI) rather than in controls [82].…”
Section: Vwf In Metabolic and Cardiovascular Disease: Animal Modelmentioning
confidence: 99%
“…Several studies in initially healthy subjects showed rather weak associations between vWF levels and CVD risk that did not always reach statistical significance. This association becomes much stronger in patients with pre-existing vascular disease, particularly survivors of myocardial infarction (MI) and patients with type 1 and 2 diabetes (Sadler 1998, Franchini and Lippi 2007, Spiel et al 2008, and the association between vWF levels and cardiovascular risk was found to be stronger in smokers compared to non-smokers (Lip and Blann 1995, Blann et al 1997a, Whincup et al 2002, Blann 2006, Vischer 2006, Franchini and Mannucci 2008, Frankel et al 2008, Spiel et al 2008, Paulinska et al 2009, van Galen et al 2012, Lenting et al 2013, Sonneveld et al 2015. Evidence for an association between elevated blood levels of vWF and respiratory diseases is rather limited, and no significant correlation between serum vWF levels and subsequent decline in FEV 1 was found, indicating that vWF is not a suitable predictor for increased risk of accelerated decline in FEV 1 (O'Callaghan et al 2005).…”
Section: Von Willebrand Factor (Vwf)mentioning
confidence: 99%